PENGARUH PARTISIPASI PENYUSUNAN ANGGARAN, KEJELASAN SASARAN ANGGARAN, DAN AKUNTABILITAS PUBLIK TERHADAP KINERJA MANAJERIAL SKPD (STUDI PADA SKPD PEMERINTAH DAERAH KABUPATEN LIMA PULUH KOTA) - Arum, Natya Sekar; Setiawan, Raja Adri; Hanif, Rheny Afriana (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2016)
This studyaimed to examine the effect of budgeting participation, the effect of budget goal and public accountability to managerial performance SKPD on goverment Lima Puluh Kota. This study uses a purposive sampling method with 96 respondents. Data collection techniques in this study is in the form of questionnaires, while data analysis technique used is multiple regression analysis were processed with SPSS version 17 for windows. From the results of the testing that has been done, simultaneous regression test (F test) showed that all independent variables studied have a simultaneous effect on managerial performance SKPD. Partial regression test (t test) showed that the variables budgeting participation and effect of budgeting goal are partially affect the variablelocal managerial performance SKPD,while public accountability variables do not affect the variables local managerial performance SKPD.Keywords: bugeting participation, effect of bugeting goal, public accountability, managerial and performance on SKPD.